2013
DOI: 10.1111/nicc.12003
|View full text |Cite
|
Sign up to set email alerts
|

Sedation practice in Nordic and non‐Nordic ICUs: a European survey

Abstract: Our study raises awareness of current sedation practice, paving the way towards optimized ICU sedation management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 53 publications
4
71
2
2
Order By: Relevance
“…A review of previous surveys [2, 3, 610] informed development of the survey tool (Additional file 1: Figure S1), which captured information on management of sedation as well as the use of specific sedative and analgesic agents. With respect to analgesia, the focus was on analgesic agents with a sedative effect, such as intravenous opioids, rather than on oral or regional analgesia.…”
Section: Methodsmentioning
confidence: 99%
“…A review of previous surveys [2, 3, 610] informed development of the survey tool (Additional file 1: Figure S1), which captured information on management of sedation as well as the use of specific sedative and analgesic agents. With respect to analgesia, the focus was on analgesic agents with a sedative effect, such as intravenous opioids, rather than on oral or regional analgesia.…”
Section: Methodsmentioning
confidence: 99%
“…Today's sedation practices have moved from a deeper towards a lighter sedation regimen. This is something to consider as patients are more awake and thus sensitive to the surrounding space (Egerod et al, 2013).…”
Section: Critical Reflectionsmentioning
confidence: 99%
“…[8] It needed eligible training that seemed generally scarce. Recently, some surveys showed that[91011] a number of patients in the ICUs still suffered from pain and inappropriate sedation treatment, and the rate of delirium assessment was still low. About 10 years ago, some surveys showed that[112] most of the patients did not get enough treatment for pain, agitation, and delirium (PAD) in China.…”
Section: Introductionmentioning
confidence: 99%